KENDALA GURU PAUD MENGEMBANGKAN SENTRA MEMBACA DAN MENULIS (STUDI KASUS DI JAKARTA TIMUR 2018) - Yubaedi Siron (UPI Kampus Cibiru, 2019)
Early childhood is the important stage entire human life-span. Early writing and reading in early childhood is the one of critical aspect to develop. Teachers should improve the environment which support to the children in literacy. The objective of this study is to describe the obstacles of early childhood teachers to develop reading and writing center for the children. This study used qualitative method which involved 27 early childhood teachers in East Jakarta. Purpossive sampling method was used, while data analyze used Miles and Huberman technique to data reduction, data display, and verification. This study revealed the experience of early childhood teacher obstacles to develop reading and writing center. It include the obstacle of preparing media of reading and writing, difficultes to manage play environment, improve library center, creating an appropriate book for children, and developing media for listening activities.